A nanoscale metal organic frameworks-based vaccine synergises with PD-1 blockade to potentiate anti-tumour immunity - Xia Li (Nature Portfolio, 2020)
Nanoparticle-based strategies have been proposed to enhance the benefit of cancer immunotherapy. Here the authors show that a cancer vaccine based on metal organic frameworks-gated mesoporous silica nanoparticles for antigen and immune potentiators delivery boosts the therapeutic efficacy of low-dose anti-PD1.